Non-violence in Buddha’s teaching and Deviation in Practice - Bajracharya, Ashok Nanda (Historical Journal, 2024)
Buddhism consistently advocates for love and respect for all living beings and stands as an animal-friendly religion. Buddha’s Pañcaśīla and other teachings focus on love and compassion for nature, including animals and plants. Maitri, Karuṇā, muditā, and upekṣā are among the main essences of Buddhism, emphasizing love, sympathy, empathy, and respect for all living beings. However, some Buddhist practices involve animal sacrifice in the name of ’Bali’ for religious purposes, and some Buddhists consume animal meat, which is unsympathetic and merciless and contradicts Buddhist and environmental ethics. This paper highlights how these practices deviate from the Buddha’s core teachings on non-violence and their significant impact on the environment and human health. The study is carried out using qualitative research methodology, with discussion and analysis conducted through the inductive method.